Perencanaan Aplikasi Berbasis Website Penjualan Online Toko Pakaian Menggunakan ReactJS: - Zakie Nurfaiz Ramadhan; Imanda, Rahmi (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Technological advancements have transformed shopping patterns from conventional to online, yetmany businesses still lack an effective e-commerce platform. This research aims to develop awebsite-based e-commerce system for clothing stores using ReactJS. The system developmentemploys the Waterfall method with stages of design, implementation, and testing. The design utilizesUse Case Diagrams and Sequence Diagrams, while testing is conducted using Black Box Testingmethodology. The result of this research is an e-commerce platform that simplifies transactions,product management, and customer management, thereby increasing business efficiency and digitalmarket reach effectively and efficiently. This platform also provides customers with a moreconvenient and faster online shopping experience.